Application for acoustic assessment: A pilot study in Parkinson’s patients - Boonyaban, Worapol; Trevittaya, Piyawat; Theera-Umpon, Nipon; Teeyapan, Kasemsit; Wantaneeyawong, Chayasak; Boonsong, Anuwat (Journal of Associated Medical Sciences, 2024)
Background: Patients with Parkinson’s disease (PD) often experience speech impairment that impacts their daily lives. In speech therapy for PD patients, it is important to use instruments to evaluate acoustic characteristics and support rehabilitation programs. However, in Thailand, access to acoustic assessment instruments is limited due to their high price and lack of portability. Objectives: This study’s aim was to develop an application for acoustic assessment (AAA) and to conduct a pilot study of the application among healthy aging (HA) and aging PD subjects. Materials and methods: This study was a developmental research design comprising three distinct phases. Phase one focused on the development of the AAA and evaluation of the accuracy and precision of the application. In phase two, a comparative analysis was conducted between AAA and Praat, a speech analysis software package, among twenty HA. Five acoustic parameters: loudness, jitter, shimmer, high frequency (Hf0), and low frequency (Lf0), were used to determine concurrent validity. Phase three compared both AAA and Praat with twenty aging PD subjects, examining the concurrent validity and reliability, and comparing the acoustic parameters of HA users with those of the aging PD cohort. Results: In phase one, the AAA shows strong accuracy ranging from 96.86% to 99.59% and high precision, with a Coefficient of Variation (%CV) of 1.65%-3.78%. In phase two, the concurrent validity of AAA compared with Praat in HA exhibited significant and very strong correlations (rs ≥ 0.90, p > 0.05) in all acoustic parameters, except for shimmer, which showed significant and strong correlations (rs = 0.73, p = 0.00). In phase three, the concurrent validity of AAA compared with Praat in aging PD subjects exhibited significant and very strong correlations (rs ≥ 0.90, p > 0.05) in loudness, Hf0, and Lf0, whereas significant and strong correlations were shown in jitter (rs = 0.85, p = 0.00) and shimmer (rs = 0.82, p = 0.00). The Intraclass Correlation Coefficient (ICC) exhibited excellent reliability in all acoustic parameters (r > 0.90). When comparing the HA and aging PD subjects using AAA, significant differences (p < 0.05) were observed in all acoustic parameters, except for Lf0 (p < 0.55). Conclusion: The AAA demonstrates high concurrent validity and reliability. It can effectively be utilized for testing in PD groups, serving as an alternative tool for evaluating acoustic characteristics and aiding in treatment planning.